Screening of phospholipase A activity and its production by new actinomycete strains cultivated by solid-state fermentation - Sutto-Ortiz, Priscila; Camacho-Ruiz, María de los Angeles; Kirchmayr, Manuel R.; El Alaoui, Meddy; Camacho-Ruiz, Rosa María; Mateos-Díaz, Juan Carlos; Noiriel, Alexandre; Carrière, Frédéric; Abousalham, Abdelkarim; Rodríguez, Jorge A. (PeerJ, 2017)
Novel microbial phospholipases A (PLAs) can be found in actinomycetes which have been poorly explored as producers of this activity. To investigate microbial PLA production, efficient methods are necessary such as high-throughput screening (HTS) assays for direct search of PLAs in microbial cultures and cultivation conditions to promote this activity. About 200 strains isolated with selected media for actinomycetes and mostly belonging to Streptomyces (73%) and Micromonospora (10%) genus were first screened on agar-plates containing the fluorophore rhodamine 6G and egg yolk phosphatidylcholine (PC) to detect strains producing phospholipase activity. Then, a colorimetric HTS assay for general PLA activity detection (cHTS-PLA) using enriched PC (≈60%) as substrate and cresol red as indicator was developed and applied; this cHTS-PLA assay was validated with known PLAs. For the first time, actinomycete strains were cultivated by solid-state fermentation (SSF) using PC as inductor and sugar-cane bagasse as support to produce high PLA activity (from 207 to 2,591 mU/g of support). Phospholipase activity of the enzymatic extracts from SSF was determined using the implemented cHTS-PLA assay and the PC hydrolysis products obtained, were analyzed by TLC showing the presence of lyso-PC. Three actinomycete strains of the Streptomyces genus that stood out for high accumulation of lyso-PC, were selected and analyzed with the specific substrate 1,2-α-eleostearoyl-sn-glycero-3-phosphocholine (EEPC) in order to confirm the presence of PLA activity in their enzymatic extracts. Overall, the results obtained pave the way toward the HTS of PLA activity in crude microbial enzymatic extracts at a larger scale. The cHTS-PLA assay developed here can be also proposed as a routine assay for PLA activity determination during enzyme purification,directed evolution or mutagenesis approaches. In addition, the production of PLA activity by actinomycetes using SSF allow find and produce novel PLAs with potential applications in biotechnology.
Keywords: Phospholipase A; Phospholipids; Actinomycetes; High-throughput screening; Solid-state fermentation